Mortar material based on fiber reinforcement and preparation system thereof

By introducing fibers and appropriate amount of recycled sand into cement mortar and adjusting the material ratio, the problem of insufficient performance of mortar material after recycled sand replaces natural sand is solved, and mortar materials with high compressive strength and flexural strength are achieved, which are suitable for a variety of mortar materials. Engineering demand and reduce production costs.

CN119118579AInactive Publication Date: 2024-12-13DONGGUAN CITY COLLEGE +1

Patent Information

Application Number
CN202411257825.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is a lack of systematic research on the performance and application of recycled sand in cement mortar in the prior art. Especially after recycled sand replaces natural sand, the performance and application of mortar materials have not been effectively explored.

Method used

Using a fiber-reinforced mortar material, including cement, gravel and fiber, the proportion of recycled sand in the sand and gravel can be 30%, 60% or 100%. Through a specific preparation system and detection module, the raw material ratio can be adjusted to Improve compressive strength and flexural strength.

Benefits of technology

It has achieved the provision of mortar materials with high compressive strength and flexural strength while ensuring economic benefits, which is suitable for different engineering needs and reduces the production cost of mortar materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118579A_ABST
    Figure CN119118579A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building materials, in particular to a fiber-reinforced mortar material and a preparation system thereof.The mortar material comprises, by weight, 1 part of cement, 3 parts of gravel, 0.65 part of tap water and 0.01-0.03 part of fiber, the gravel comprises natural sand and reclaimed sand, and the proportion of the reclaimed sand in the gravel is 30%, 60% or 100%. According to the scheme, for the performance and application of reclaimed sand in cement mortar after natural sand is replaced, systematic research is given, different material proportions can be set according to different engineering requirements by referring to the research result of the scheme, mortar materials suitable for different projects can be produced, and the production cost of the mortar materials can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a fiber-reinforced mortar material and a preparation system thereof. Background Art

[0002] The construction waste brought by urban and rural construction is increasing year by year, which has a negative impact on the green and healthy development of urbanization in my country. By recycling and transforming building materials, many components in construction waste can be recycled, which can not only make effective use of construction waste and improve the environment, but also solve the problem of resource shortage.

[0003] For example, the prior art CN109553368A discloses a recycled concrete comprising the following components in parts by mass: 10-12 parts of water; 20-25 parts of cement; 1-2 parts of water reducer; 7-8 parts of microsilica powder; 40-50 parts of recycled aggregate, which is a mixture of broken bricks and stones, waste concrete blocks and industrial waste slag; 60-80 parts of natural aggregate; 10-15 parts of waste textile fibers; and 1-2 parts of coupling agent.

[0004] Another typical example is the crack-resistant recycled concrete disclosed in the prior art CN113603422A, which is made from the following raw materials: silicate cement, rice husk ash 1, natural fine aggregate, natural coarse aggregate, recycled coarse aggregate, water, water reducer, modified rubber powder, and amino silicone oil modified steel fiber, wherein the modified rubber powder is made by reacting waste rubber powder and rice husk ash 2 in a sodium hydroxide solution.

[0005] Let's look at the method, system and apparatus for processing recycled concrete aggregate (RCA) disclosed in the prior art of CN116710415A, including a computer program encoded on a computer storage medium. One of the methods includes: obtaining a first optical measurement of the RCA particles; determining an initial characteristic representation of the RCA particles; iteratively performing a carbonation process on the RCA particles, obtaining a second optical measurement of the RCA particles, and determining a second characteristic representation of the RCA particles, wherein the conditions of the carbonation process are initially set based on the initial characteristic representation, and the conditions of the carbonation process are adjusted based on the second characteristic representation; iteratively performing a densification process on the RCA particles, obtaining a third optical measurement of the RCA particles, and determining a third characteristic representation of the RCA particles, wherein the conditions of the densification process are initially set based on the initial characteristic representation or the second characteristic representation, and the conditions of the densification process are adjusted based on the third characteristic representation.

[0006] In the current research field, there is relatively little in-depth exploration of regenerated sand, and the main research focus is on the performance test of recycled concrete. However, there has been no systematic study on the performance and application of regenerated sand in cement mortar after replacing natural sand. In order to solve the common problems in this field, the present invention is made. Summary of the invention

[0007] The purpose of the present invention is to propose a fiber-reinforced mortar material and a preparation system thereof in view of the current deficiencies.

[0008] In order to overcome the shortcomings of the prior art, the present invention adopts the following technical solutions:

[0009] A fiber-reinforced mortar material, comprising, by weight, 1 part of cement, 3 parts of sand and gravel, 0.65 parts of tap water, and 0.01-0.03 parts of fiber, wherein the sand and gravel comprise natural sand and regenerated sand, and the regenerated sand accounts for 30%, 60%, or 100% of the sand and gravel;

[0010] The natural sand is made of river sand, and the apparent density of the river sand is 2654kg / m 3 , bulk density is 1495kg / m 3 , the mud content is 7.5% and the fineness modulus is 3.1, and the strength grade of the cement is PP32.5R;

[0011] The fiber is polypropylene fiber. The model of the polypropylene fiber is HC19, and its tensile strength is 469MPa, the ultimate elongation is 28.4%, the elastic modulus is 4236MPa, and the density is 0.91g / cm 3 , diameter is 32.7mm, melting point is 169℃.

[0012] Furthermore, the fiber is 0.01 parts and the proportion of reclaimed sand in the gravel is 60%.

[0013] A fiber-reinforced mortar material preparation system for realizing the mortar material, the preparation system comprising a mold, a planetary mixer, a vibrating table, wooden strips, steel needles, a curing machine and a detection module, the mold being a rectangular container, the mold being used to shape cement mortar, the planetary mixer being used to stir various raw materials, the vibrating table being used to vibrate the cement mortar in the mold, the wooden strips and steel needles being used to flatten the surface of the cement mortar, the curing machine being used to preserve the finished mortar material, and the detection module being used to detect the performance of the finished mortar material.

[0014] Furthermore, the detection module includes a digital measuring instrument, a consistency meter, an electronic balance, a press and a three-point bending testing machine. The digital measuring instrument is used to detect the length, width and height of the finished mortar material, the consistency meter is used to detect the consistency of the finished mortar material, the electronic balance is used to weigh the finished mortar material, the press is used to detect the compressive strength of the finished mortar material, and the three-point bending testing machine is used to detect the flexural strength of the finished mortar material.

[0015] Furthermore, a method for preparing a mortar material is also provided, comprising the following steps:

[0016] S1, prepare corresponding raw materials and mix the raw materials according to volume ratio;

[0017] S2, using a planetary mixer to stir the mixed raw materials to obtain mortar;

[0018] S3, cleaning the mold, applying a release agent on the inner side of the mold, and pouring the stirred mortar into the mold;

[0019] S4, vibrate the mold. If the mold is not filled after vibration, return to S2. Otherwise, execute S5;

[0020] S5, scraping the mortar on the surface of the mold with a wooden strip or a steel needle;

[0021] S6, leaving the mold still, and demoulding and sampling the mortar after it solidifies and forms;

[0022] S7, placing the demoulding sampled mortar in a curing machine for curing, and obtaining a finished mortar material after the curing is completed;

[0023] S8, obtaining the length, width, height, initial value of compressive strength and initial value of flexural strength of the finished mortar material;

[0024] S9, obtaining respective error parameters when the pressure transmission direction of the finished mortar material is along the height, length and width of the finished mortar material;

[0025] S10, obtaining the corrected compressive strength and flexural strength according to the initial value obtained in S8 and the error parameter obtained in S9;

[0026] S11, determine whether the corrected compressive strength and flexural strength are within the required range, if yes, use the weight ratio of each raw material in the finished mortar material as the final ratio; otherwise, adjust the weight ratio of each raw material in the mortar material and return to S1.

[0027] The beneficial effects achieved by the present invention are: 1. This scheme provides a systematic study on the performance and application of recycled sand in cement mortar after replacing natural sand. By drawing on the research results of this scheme, different material ratios can be set according to different engineering requirements and mortar materials suitable for different projects can be produced, which is conducive to reducing the cost of mortar material production.

[0028] 2. The mortar material produced according to the ratio given in this scheme has higher compressive strength and flexural strength by introducing fibers and an appropriate amount of regenerated sand. While ensuring high economic benefits, it can meet most engineering needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention can be further understood from the following description in conjunction with the accompanying drawings. The components in the figures are not necessarily drawn to scale, but the emphasis is placed on illustrating the principles of the embodiments. In different views, the same reference numerals designate the same parts.

[0030] Figure 1 It is a schematic structural diagram of the preparation system of the present invention.

[0031] Figure 2 It is the experimental material data table of the present invention.

[0032] Figure 3 This is a table of test results of mortar consistency of different experimental groups of the present invention.

[0033] Figure 4 The table is a table of the test results of density, compressive strength and flexural strength of different experimental groups of the present invention.

[0034] Figure 5 For the present invention Figure 4 Table of averaged data and its corresponding scatter plot.

[0035] Figure 6 Schematic diagram of the finished mortar material when WC(z) is the error parameter in the compression test.

[0036] Figure 7 Schematic diagram of the finished mortar material in the flexural test when WT(z,x) is the error parameter. DETAILED DESCRIPTION

[0037] The following is an explanation of the embodiments of the present invention through specific embodiments. Those skilled in the art can understand the advantages and effects of the present invention from the contents disclosed in this specification. The present invention can be implemented or applied through other different specific embodiments, and the details in this specification can also be modified and changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. In addition, the drawings of the present invention are only simple schematic illustrations and are not depicted according to actual sizes. It is stated in advance. The following embodiments will further explain the relevant technical contents of the present invention in detail, but the disclosed contents are not intended to limit the scope of protection of the present invention.

[0038] Embodiment 1: According to Figure 1 , Figure 2 , Figure 3 and Figure 4, this embodiment provides a fiber-reinforced mortar material, the mortar material includes 1 part of cement, 3 parts of sand and gravel, 0.65 parts of tap water and 0.01-0.03 parts of fiber by weight, the sand and gravel include natural sand and regenerated sand, and the regenerated sand accounts for 30%, 60% or 100% of the sand and gravel;

[0039] Preferably, the fiber content is 0.01 parts and the regenerated sand accounts for 60% of the sand and gravel. At this time, the mortar density of the prepared mortar material is 1859.1 kg / m 3 , the consistency is 6.4mm, the compressive strength is 16.3MPa, and the flexural strength is 3.9MPa. The mortar density of the mortar material made by the above ratio is 1859.1kg / m 3 The consistency is 6.4mm, the compressive strength is 16.3MPa (equivalent to 86.2% of the mortar material made by the benchmark mix ratio), and the flexural strength is 3.9MPa (equivalent to 92.9% of the mortar material made by the benchmark mix ratio). By adopting low-cost recycled sand, its economic benefits are ideal and can meet most engineering performance requirements; the benchmark mix ratio is 1 part of cement, 3 parts of natural sand and 0.65 parts of tap water by weight.

[0040] Specifically, the stronger the flexural strength and compressive strength, the better the performance of the material, which can be combined with Figure 4 as well as Figure 5 , the ratio of raw materials is adjusted according to the compressive strength, flexural strength, density and cost required by the comprehensive project to meet the needs of different projects. For example: when no fiber is added, reducing the amount of regenerated sand can improve the compressive strength. When the fiber content is below 3%, adjusting the content of regenerated sand in the sand and gravel to close to 60% can improve the compressive strength. When regenerated sand is added, adjusting the fiber content to close to 1% and the regenerated sand content to close to 6% can comprehensively improve various capabilities.

[0041] Specifically, the regenerated sand comes from old sand that has been harmlessly treated in casting production. The treatment method belongs to the prior art. For details, reference may be made to the method proposed in CN115846588A, which will not be elaborated here.

[0042] The natural sand is made of river sand, and the apparent density of the river sand is 2654kg / m 3 , bulk density is 1495kg / m 3 , the mud content is 7.5% and the fineness modulus is 3.1, and the strength grade of the cement is PP32.5R; the optional values ​​of the proportion of regenerated sand in natural sand are 30%, 60% and 100%, and the optional values ​​of the fiber content are 0.01, 0.02 and 0.03.

[0043] Furthermore, the fiber is a polypropylene fiber, the model of the polypropylene fiber is HC19, the tensile strength is 469MPa, the ultimate elongation is 28.4%, the elastic modulus is 4236MPa, and the density is 0.91g / cm 3 , diameter is 32.7mm, melting point is 169℃.

[0044] Furthermore, it also includes a fiber-reinforced mortar material preparation system for realizing the mortar material, the system including a mold, a planetary mixer, a vibrating table, wooden strips, steel needles, a curing machine and a detection module, the mold is a rectangular container, the mold is used to shape the cement mortar, the planetary mixer is used to stir various raw materials, the vibrating table is used to vibrate the cement mortar in the mold, the wooden strips and steel needles are used to scrape the surface of the cement mortar, the curing machine is used to preserve the finished mortar material, and the detection module is used to detect the performance of the finished mortar material.

[0045] Specifically, the mold is a rectangular container with a length of 40 mm, a width of 40 mm, and a height of 160 mm.

[0046] Furthermore, the detection module includes a digital measuring instrument, a consistency meter, an electronic balance, a press and a three-point bending testing machine. The digital measuring instrument is used to detect the length, width and height of the finished mortar material, the consistency meter is used to detect the consistency of the finished mortar material, the electronic balance is used to weigh the finished mortar material, the press is used to detect the compressive strength of the finished mortar material, and the three-point bending testing machine is used to detect the flexural strength of the finished mortar material.

[0047] Specifically, the consistency meter can be an SC-145 digital mortar consistency meter pointer ordinary measuring instrument fluidity tester; the press can be a hydraulic press; by combining the weighing result of the electronic balance and the volume of the mold, and combining with the existing density calculation formula, the density of the finished mortar material can be obtained; the compressive strength can be obtained by applying pressure to one side of the material and measuring the maximum load that the material can withstand before it fails, and the flexural strength can be obtained by supporting the material and applying a load in the middle of the material, and observing the maximum load that the material can withstand before it fails.

[0048] Specifically, in addition to the ratio given in claim one, this scheme also studies mortar materials with different ratios. Through orthogonal experimental design, this scheme conducts a total of 16 groups of experiments, and tests the performance of finished mortar materials obtained when the recycled sand replacement rate is 0%, 30%, 60% and 100%, and the fiber content is 0, 0.1%, 0.2% and 0.3%, thereby obtaining the performance of the finished mortar materials under different ratios, and then screening out the material ratio corresponding to the finished mortar material with the best performance. No systematic research has been conducted in the prior art.

[0049] Specifically, this program sets up a total of 16 groups of experiments. Figure 2 This is the experimental material data chart. Figure 3 This is the test result table of mortar consistency of different experimental groups. Figure 4 This is a table showing the test results of density, compressive strength and flexural strength of different experimental groups. Figure 5 For Figure 4 The table after the data is averaged and its corresponding scatter plot;

[0050] The following is an example of averaging: Figure 5 The density corresponding to 0% fiber content is 1898.525, which is Figure 4 The average result of the density values ​​(1867.6+1925.1+1884.6+1916.8) corresponding to the medium fiber content of 0% (group sequence 1 to 4).

[0051] Furthermore, a method for preparing a mortar material is also provided, comprising the following steps:

[0052] S1, prepare corresponding raw materials and mix the raw materials according to volume ratio;

[0053] S2, using a planetary mixer to stir the mixed raw materials to obtain mortar;

[0054] S3, cleaning the mold, applying a release agent on the inner side of the mold, and pouring the stirred mortar into the mold;

[0055] S4, vibrate the mold, if the mold is not filled after vibration, return to S2, otherwise, S5;

[0056] S5, scraping the mortar on the surface of the mold with a wooden strip or a steel needle;

[0057] S6, leaving the mold still, and demoulding and sampling the mortar after it solidifies and forms;

[0058] S7, placing the demoulding sampled mortar in a curing machine for curing, and obtaining a finished mortar material after the curing is completed.

[0059] S8, obtaining the length, width, height, initial value of compressive strength and initial value of flexural strength of the finished mortar material;

[0060] S9, obtaining respective error parameters when the pressure transmission direction of the finished mortar material is along the height, length and width of the finished mortar material;

[0061] S10, obtaining the corrected compressive strength and flexural strength according to the initial value obtained in S8 and the error parameter obtained in S9;

[0062] S11, determine whether the corrected compressive strength and flexural strength are within the required range, if yes, use the weight ratio of each raw material in the finished mortar material as the final ratio; otherwise, adjust the weight ratio of each raw material in the mortar material and return to S1.

[0063] Specifically, the curing time is 28 days, the curing temperature is 18° C. to 22° C., and the curing relative humidity is 90%.

[0064] The beneficial effects of this scheme are as follows: 1. This scheme provides a systematic study on the performance and application of recycled sand in cement mortar after replacing natural sand. By drawing on the research results of this scheme, different material ratios can be set according to different engineering requirements and mortar materials suitable for different projects can be produced, which is conducive to reducing the cost of mortar material production.

[0065] 2. The mortar material produced according to the ratio given in this scheme has higher compressive strength and flexural strength by introducing fibers and an appropriate amount of regenerated sand. While ensuring high economic benefits, it can meet most engineering needs.

[0066] Embodiment 2: This embodiment should be understood to include all the features of any of the foregoing embodiments, and further improve upon them. In Embodiment 1, the sample used to test the compressive strength of the mortar material is a rectangular mortar material with a length of 40 mm, a width of 40 mm, and a height of 160 mm. The sample used to test the flexural strength of the mortar material is a cubic mortar material with a length of 70.7 mm, a width of 70.7 mm, and a height of 70.7 mm. When testing mortar materials of the same size in different placement methods or mortar materials of different sizes, the pressure transfer speed in the material is different, which may cause experimental errors. Therefore, this embodiment proposes a preferred calculation method for compressive strength and flexural strength in the process of testing the compressive strength and flexural strength of the finished mortar material to reduce the influence of the error on the experimental results:

[0067] The preparation system also includes the following steps in steps S8 to S10:

[0068] Get the initial value of the compressive strength:

[0069] Among them, f is the initial value of compressive strength, P is the maximum load applied at failure, A is the stress-bearing area of ​​the finished mortar material, and the direction of pressure propagation is from the top (stress-bearing surface) of the finished mortar material to the bottom surface. The error parameter WC(z) is calculated by the following formula:

[0070]

[0071] like Figure 6 , WC(z) is the error parameter when the pressure transmission direction of the finished mortar material is along the height (z) of the finished mortar material, x is the length of the finished mortar material, y is the width of the finished mortar material, z is the height of the finished mortar material, f(x) is the initial value of the compressive strength obtained when the pressure transmission direction is along the length of the finished mortar material (the bottom area is y*z), f(y) is the initial value of the compressive strength obtained when the pressure transmission direction is along the width of the finished mortar material (the bottom area is x*z), and f(z) is the initial value of the compressive strength obtained when the pressure transmission direction is along the height of the finished mortar material (the bottom area is y*x);

[0072]

[0073] WC(x) is the error parameter when the pressure transmission direction of the finished mortar material is along the length (x) of the finished mortar material, and WC(y) is the error parameter when the pressure transmission direction of the finished mortar material is along the width (y) of the finished mortar material.

[0074] The corrected compressive strength KYQD is:

[0075]

[0076] Specifically, when the fiber content or the regenerated sand content changes, it is necessary to re-acquire data such as f(x) to obtain the corrected compressive strength;

[0077] Optimized calculation method for flexural strength:

[0078] The initial value of the flexural strength is obtained as

[0079] Where: g is the initial value of the flexural strength, x is the length of the finished mortar material (i.e., the support spacing), y is the width of the finished mortar material, z is the height of the finished mortar material, and the direction of pressure propagation is from the top (stress-bearing surface) of the finished mortar material to the bottom surface and both ends of the length. The error parameter WT(z,x) is calculated according to the following formula:

[0080]

[0081] The detection module also includes a clamp, which is clamped on both sides of the finished mortar material during the compressive strength test, and the press applies pressure from the top to the bottom of the finished mortar material. Figure 7 , WT(z,x) is the error parameter when the pressure is transmitted from the top to the bottom when the clamping direction is the left and right sides of the finished mortar material in the figure, that is, WT(z,x) is the error parameter when the clamping position is the two long sides (x) direction, and the pressure transmission direction of the finished mortar material is transmitted along the height (z) of the finished mortar material to the bottom surface (xy) of the finished mortar material. g(z,x) is the initial value of the flexural strength obtained when the pressure transmission direction of the finished mortar material is the pressure-bearing surface along the height (z) of the finished mortar material to the bottom surface and the two ends of the length (x). g(x,y) is the initial value of the flexural strength obtained when the pressure transmission direction of the finished mortar material is the pressure-bearing surface along the length (x) of the finished mortar material to the bottom surface and the two ends of the width (y). g(y,z) is the initial value of the flexural strength obtained when the pressure transmission direction of the finished mortar material is the pressure-bearing surface along the width (y) of the finished mortar material to the bottom surface and the two ends of the height (z).

[0082] g(y,x) is the initial value of the flexural strength obtained when the pressure transmission direction of the finished mortar material is from the stress-bearing surface along the width (y) of the finished mortar material to the bottom surface and both ends of the length (x); g(z,y) is the initial value of the flexural strength obtained when the pressure transmission direction of the finished mortar material is from the stress-bearing surface along the height (z) of the finished mortar material to the bottom surface and both ends of the width (y); g(x,z) is the initial value of the flexural strength obtained when the pressure transmission direction of the finished mortar material is from the stress-bearing surface along the length (x) of the finished mortar material to the bottom surface and both ends of the height (z);

[0083] WT(y, z) is the error parameter when the pressure transmission direction of the finished mortar material is transmitted along the width (y) of the finished mortar material to the bottom of the finished mortar material when the clamping position is in the direction of the two high sides (z):

[0084]

[0085] WT(x, y) is the error parameter when the clamping position is in the direction of the two long sides (x), and the pressure transmission direction of the finished mortar material is transmitted along the width (y) of the finished mortar material to the bottom of the finished mortar material:

[0086]

[0087] The corrected compressive strength KYQD is:

[0088]

[0089] Specifically, when the fiber content or the regenerated sand content changes, it is necessary to re-acquire the above data such as g(z,x) to obtain the corrected compressive strength.

[0090] The beneficial effects of this embodiment are as follows: by calculating the error by referring to the compressive strength and flexural strength obtained under different conditions, and adjusting the final calculation result according to the error, it is helpful to reduce the error caused by different stress conditions and to improve the accuracy of the final calculation result.

[0091] The above disclosed contents are only preferred feasible embodiments of the present invention, and do not limit the protection scope of the present invention. Therefore, all equivalent technical changes made by using the contents of the present invention specification and drawings are included in the protection scope of the present invention. In addition, the elements therein can be updated with the development of technology. The above units are only examples. Those skilled in the art can use corresponding units according to different designs according to actual needs when implementing this solution.

Claims

1. A fiber-reinforced mortar material, characterized in that: The mortar material includes 1 part of cement, 3 parts of sand and gravel, 0.65 parts of tap water and 0.01-0.03 parts of fiber in a weight ratio, wherein the sand and gravel include natural sand and regenerated sand, and the regenerated sand accounts for 30%, 60% or 100% of the sand and gravel; The natural sand is made of river sand, and the apparent density of the river sand is 2654kg / m 3 , bulk density is 1495kg / m 3 , the mud content is 7.5% and the fineness modulus is 3.1, and the strength grade of the cement is PP32.5R; The fiber is polypropylene fiber. The model of the polypropylene fiber is HC19, and its tensile strength is 469MPa, the ultimate elongation is 28.4%, the elastic modulus is 4236MPa, and the density is 0.91g / cm 3 , diameter is 32.7mm, melting point is 169℃.

2. A fiber-reinforced mortar material according to claim 1, characterized in that: The fiber content is 0.01 parts and the proportion of reclaimed sand in the gravel is 60%.

3. A fiber-reinforced mortar material preparation system for realizing the mortar material according to claim 2, characterized in that: The preparation system includes a mold, a planetary mixer, a vibrating table, wooden strips, steel needles, a curing machine and a detection module. The mold is a rectangular container, the mold is used to shape cement mortar, the planetary mixer is used to stir various raw materials, the vibrating table is used to vibrate the cement mortar in the mold, the wooden strips and steel needles are used to scrape the surface of the cement mortar, the curing machine is used to preserve the finished mortar material, and the detection module is used to detect the performance of the finished mortar material.

4. A fiber-reinforced mortar material preparation system according to claim 3, characterized in that: The detection module includes a digital measuring instrument, a consistency meter, an electronic balance, a press and a three-point bending testing machine. The digital measuring instrument is used to detect the length, width and height of the finished mortar material, the consistency meter is used to detect the consistency of the finished mortar material, the electronic balance is used to weigh the finished mortar material, the press is used to detect the compressive strength of the finished mortar material, and the three-point bending testing machine is used to detect the flexural strength of the finished mortar material.

5. A fiber-reinforced mortar material preparation system according to claim 4, characterized in that: Also included is a method for preparing a mortar material, comprising the following steps: S1, prepare corresponding raw materials and mix the raw materials according to volume ratio; S2, using a planetary mixer to stir the mixed raw materials to obtain mortar; S3, cleaning the mold, applying a release agent on the inner side of the mold, and pouring the stirred mortar into the mold; S4, vibrate the mold. If the mold is not filled after vibration, return to S2. Otherwise, execute S5; S5, scraping the mortar on the surface of the mold with a wooden strip or a steel needle; S6, leaving the mold still, and demoulding and sampling the mortar after it solidifies and forms; S7, placing the demoulding sampled mortar in a curing machine for curing, and obtaining a finished mortar material after the curing is completed; S8, obtaining the length, width, height, initial value of compressive strength and initial value of flexural strength of the finished mortar material; S9, obtaining respective error parameters when the pressure transmission direction of the finished mortar material is along the height, length and width of the finished mortar material; S10, obtaining the corrected compressive strength and flexural strength according to the initial value obtained in S8 and the error parameter obtained in S9; S11, determine whether the corrected compressive strength and flexural strength are within the required range, if yes, use the weight ratio of each raw material in the finished mortar material as the final ratio; otherwise, adjust the weight ratio of each raw material in the mortar material and return to S1.

Citation Information

Patent Citations

  • Production process of PC component

    CN108726967A

  • Fiber reinforced regenerated fine aggregate cement-based composite material

    CN110498647A

  • Method for predicting cement strength through multi-hidden-layer BP network in big data environment

    CN110705920A

  • Intelligent preparation system for RPC cover plate

    CN118205095A

Cited By

  • Method and system for predicting optimal proportion of fiber-reinforced environment-friendly cement mortar based on machine learning

    CN120998341A